2000
DOI: 10.1055/s-2000-8549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Iridoids from Plant Origin on Arachidonic Acid Metabolism in Cellular Systems

Abstract: Seven iridoid glycosides isolated from different extracts of Scrophularia scorodonia L., namely bartsioside, aucubin, harpagide, harpagoside, 8-acetylharpagide, scorodioside and scropolioside B, had been evaluated for their in vitro anti-inflammatory activity in cellular systems generating COX and LOX metabolites. Structure-activity relationships obtained from in vitro screening results were discussed. Most compounds assayed did not exhibit any significant effect on PGE2- and LTC4-release from calcium ionophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 10 publications
4
29
2
1
Order By: Relevance
“…However, some negative or non-signifi cant results have also been obtained in in vitro studies that tested varied extracts for their action on leukotrienes and prostaglandins in human or mouse blood. The results showed no significant effect on the synthesis of these eicosanoids hence on COX-2 and LOX pathways (Moussard et al, 1992;Benito et al, 2000). In addition to the varied formulation types and doses, discrepancies in the clinical results can also be related to the route of administration as well as to the type and location of infl ammation.…”
Section: Introductionmentioning
confidence: 75%
“…However, some negative or non-signifi cant results have also been obtained in in vitro studies that tested varied extracts for their action on leukotrienes and prostaglandins in human or mouse blood. The results showed no significant effect on the synthesis of these eicosanoids hence on COX-2 and LOX pathways (Moussard et al, 1992;Benito et al, 2000). In addition to the varied formulation types and doses, discrepancies in the clinical results can also be related to the route of administration as well as to the type and location of infl ammation.…”
Section: Introductionmentioning
confidence: 75%
“…This study also demonstrated that the extract inhibits LPS-induced sysnthesis of IL-6, IL-1b and PGE 2 but at concentrations of more than 100 lg of extract/ml. Several iridoid glycosides that are characteristic of Devil's Claw extracts but isolated from Scrophularia scorodonia L., including harpagide, harpagoside, 8-acetylharpagide and aucubin were tested in vitro for effects on the cyclo-oxygenase (COX) and lipo-oxygenase (LOX) pathways in isolated mouse peritoneal macrophages and human blood platelets (Benito et al, 2000). Most of the compounds that were tested did not exhibit a significant effect on the stimulated release of prostaglandin E 2 (PGE 2 ) (product of COX pathway) and of the cysteinyl-leukotriene, LTC 4 , (the major secreted product of the LOX pathway) in calcium ionophore-stimulated mouse peritoneal macrophages.…”
Section: Pharmacocological Effects -In Vitromentioning
confidence: 99%
“…Lonicera japonica (Caprifoliaceae). 12) 46.9 (C-9), 118.6 (C-10), 168.4 (C-11), 55.0 (OMe), 97.9 (C-1Ј), 73.0 (C-2Ј), 76.7 (C-3Ј), 70.0 (C-4Ј), 77.0 (C-5Ј), 61.1 (C-6Ј). Gentiana scabra (Gentianaceae).…”
Section: Biological and Pharmacological Activity Of Naturally Occurrimentioning
confidence: 99%